P55 Evaluation of NAAT and POCT for detecting Trichomonas vaginalis infection in women at a London sexual health clinic. (23rd May 2012) - Nathan, B; Heron, D; Appiah, J; Saunders, P; Brum, R; Nichols, T; Alexander, S; Baraister, P; Ison, C
Abstract : Background: TV is a common infection in our clinic, but the true prevalence is likely to be higher since microscopy-the current diagnostic test has a low sensitivity. Nucleic Acid Amplification (NAAT) and Point of Care Tests (POCT) are commercially available and are reported to have much higher sensitivities. To our knowledge this is the first study to evaluate four different tests for TV in a London Clinic. Aim: To evaluate the clinical utility of NAAT and POCT compared to microscopy and culture. Methods: All symptomatic women who presented to the clinic on Monday and Tuesday from September 2011 were invited to participate in the study. Swabs for a validated in-house NAAT, POCT ( OSOM Genzyme Diagnostics ) and culture using TV In-pouch culture system were taken. Technicians processing the POCT, NAAT and cultures were blinded to all other results. Results: A total of 247 symptomatic women were recruited over a 6-month period. 21 (8.5%) tested positive on culture, 22 (9%) on POCT and NAAT, 9 (3.6%) on microscopy. Using culture as the reference standard the sensitivities/specificities were: POCT 100% [95% CI 84 to 100]/99.6% [95% CI 97.5 to 99.9], NAAT 95.2% [95% CI 76 to 99.9]/99.1% [95% CI 96.8 to 99.9], microscopy 42.9% [95% CI 22 to 56]/100% [95% CI 98.4 to 100] and prevalence 8.5% [95% CI 5.4 to 12.8]. Using NAAT as the reference standard the sensitivities were: culture 90.9% [95% CI 71 to 98.9], POCT 95.5% [95% CI 77 to 99.9], microscopy 36.4% [95% CI 17 to 59] and prevalence 8.9% [95% CI 5.7 to 13.2]. Conclusions: The sensitivity of POCT and NAAT were as anticipated much greater than microscopy alone, resulting in a prevalence over double than previously estimated. Molecular methods for detecting TV infection in this population would diagnose a significantly greater number of women with TV. Clinics with high rates of TV may benefit from using POCT with the advantage of a rapid turn-around result over NAAT.